The vaccine adjuvant MPLA activates glycolytic metabolism in mouse mDC by a JNK-dependent activation of mTOR-signaling. (February 2019) - Blanco-Pérez, Frank; Goretzki, Alexandra; Wolfheimer, Sonja; Schülke, Stefan
Highlights: If the vaccine adjuvant MPLA can activate immune cell metabolism is mostly unknown. Stimulation of mDCs with MPLA resulted in a mTOR-dependent activation of glucose metabolism. MPLA-induced cytokine secretion was partially inhibited using mTOR- and MAP kinase-inhibitors. Activation of glucose metabolism was mTOR-dependent, but strictly MAP kinase-independent. Understanding mechanisms of immune-activation contributes to a safe application of this adjuvant. Abstract: Introduction: The detoxified TLR4-ligand MPLA is a successfully used adjuvant in clinically approved vaccines. However, its capacity to activate glycolytic metabolism in mDC and the influence of MPLA-induced metabolic changes on cytokine secretion are unknown. Aim: To analyze the capacity of MPLA to activate mDC metabolism and the mechanisms contributing to MPLA-induced metabolism activation and cytokine secretion. Methods: C57BL/6 bone-marrow-derived myeloid dendritic cells (mDCs) were stimulated with LPS or MPLA and analyzed for intracellular signaling, cytokine secretion, and metabolic state. mDC were pre-treated with rapamycin (mTOR-inhibitor), U0126, SP600125, SB202190 (MAPK kinase inhibitors), as well as dexamethasone (MAPK- and NFκB-inhibitor) and analyzed for MPLA-induced cytokine secretion and cell metabolic state. Results: Stimulation of mDCs with either LPS or MPLA resulted in a pronounced, mTOR-dependent activation of glucose metabolism characterized by induction of the Warburg Effect, increased glucose consumption from the culture medium, as well as release of LDH. Compared to LPS, MPLA induced significantly lower cytokine secretion. The activation of mDC metabolism was comparable between LPS- and MPLA-stimulated mDCs. The MPLA-induced cytokine secretion could be partially inhibited using mTOR-, MAP kinase-, and NFκB-inhibitors, whereas the activation of glucose metabolism was shown to depend on both mTOR- and JNK-signaling. Summary: The MPLA-induced activation of glycolytic metabolism in mouse mDC was shown to depend on a JNK-mediated activation of mTOR-signaling, while both MAPK- and NFB-signaling contributed to pro-inflammatory cytokine secretion. Understanding the mechanisms by which MPLA activates dendritic cells will both improve our understanding of its adjuvant properties and contribute to the future development and safe application of this promising adjuvant.